Doubts on the Hadith of Al-Thaqalayn in Sunni and Shia Perspective - Rizaka, Maghza; Pratama, Ferdy; Said, Imam Ghazali (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
The Hadith of al-Thaqalayn is one of the most significant hadiths in Islamic literature, particularly within Sunni and Shia traditions. This hadith states that the Prophet Muhammad (SAW) left behind two important things: the Qur'an and the Ahlul Bayt. This study examines various versions of the Hadith of al-Thaqalayn to determine its authenticity, interpretation, and implications for leadership in Islam. By comparing primary sources such as Ṣaḥīḥ Muslim and Uṣūl al-Kāfī, along with secondary literature, this research employs content analysis to identify textual variations, address doubts, and assess scholarly criticism of the Hadith of al-Thaqalayn. The findings reveal that despite differences in interpretation, both Sunni and Shia traditions emphasize the importance of adhering to the Qur'an and the Sunnah as the primary guides. The study also highlights the complexity of assessing the reliability of hadiths, demonstrating that even though some chains of transmission may be considered weak, the core message of adhering to the Qur'an and the teachings of the Prophet Muhammad remains vital. Additionally, the analysis discusses theological debates regarding the role of the Ahlul Bayt and provides a more comprehensive understanding of the Hadith of al-Thaqalayn within the context of Islamic scholarly tradition.